A modular system of deep level transient spectroscopy - Rusli, Nazreen; Debuf, Didier (2011)
Deep Level Transient Spectroscopy (DLTS) is a technique to determine the electrical characteristics of an electrically active defect in a semiconductor. A measurement system is developed to detect defects in a semiconductor in a LabView environment. A more accurate method namely Fundamental Frequency Deep Level Transient Spectroscopy (FFDLTS) is proposed as one of the methods to analyze the defect level depth.